Routine screening of Indigenous cancer patients' unmet support needs: a qualitative study of patient and clinician attitudes. Issue 1 (December 2016) - Thewes, B.; Davis, E.; Girgis, A.; Valery, P.; Giam, K.; Hocking, A.; Jackson, J.; He, V.; Yip, D.; Garvey, G.
Abstract Background Indigenous Australians have poorer cancer outcomes in terms of incidence mortality and survival compared with non-Indigenous Australians. The factors contributing to this disparity are complex. Identifying and addressing the psychosocial factors and support needs of Indigenous cancer patients may help reduce this disparity. The Supportive Care Needs Assessment Tool for Indigenous People (SCNAT-IP) is a validated 26-item questionnaire developed to assess their unmet supportive care needs. This qualitative study reports on patient and clinician attitudes towards feasibility and acceptability of SCNAT-IP in routine care. Methods Forty-four in-depth semi-structured interviews were conducted with 10 clinical staff and 34 Indigenous cancer patients with heterogeneous tumours. Participants were recruited from four geographically diverse Australian cancer clinics. Transcripts were imported into qualitative analysis software (NVivo 10 Software), coded and thematic analysis performed. Results Indigenous patients (mean age 54.4 years) found the SCNAT-IP beneficial and easy to understand and they felt valued and heard. Clinical staff reported multiple benefits of using the SCNAT-IP. They particularly appreciated its comprehensive and systematic nature as well as the associated opportunities for early intervention. Some staff described improvements in team communication, while both staff and patients reported that new referrals to support services were directly triggered by completion of the SCNAT-IP. There were also inter-cultural benefits, with a positive and bi-directional exchange of information and cultural knowledge reported when using the SCNAT-IP. Although staff identified some potential barriers to using the SCNAT-IP, including the time required, the response format and comprehension difficulties amongst some participants with low English fluency, these were outweighed by the benefits. Some areas for scaled improvement were also identified by staff. Conclusions Staff and patients found the SCNAT-IP to be an acceptable tool and supported universal screening for Indigenous cancer patients. The SCNAT-IP has the potential to help reduce the inequalities in cancer care experienced by Indigenous Australians by identifying and subsequently addressing their unmet support needs. Further research is needed to explore the validity of the SCNAT-IP for Indigenous people from other nations.